فعالية الطريقة القياسية بوسيلة خريطة المفاهيم على فهم النحو لدى الطلاب بمعهد دار العلوم العصري بندا أتشيه - Fajriah, Fajriah; Hilmi, Hilmi; Utari, Zulnafara Kaisa (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2023)
Based on the result of the observation and interview in class 4-D at Dayah Modern Darul 'Ulum, there had some difficulties for the students in understanding nahwu. The aim of this study is to know the effectiveness of the qiyasiyah method and concept map media to increase students’ understanding nahwu. In this study, the researcher applied the pre-experimental method through one group pre test post test design. To collect the data, the researcher used the test. The result of this research is the using of qiyasiyah method and concept map media is effective to increase students’ understanding nahwu. Furthermore, it was found that the result of the T-Test is a significance level (2- tailed) 0.00<0.05. This value shows that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected.